Analyzing the reception of Cebuano production workers on the concept of labor unionism through Lino Brocka's "Bayan Ko Kapit sa Patalim" (1984) film - Mantos, Zhynnon Mar; Lagahit, Mila Marie M.; Tañongon, Crina E.; Dayan, Gilliane Marrei P. (Cebu City College of Communication, Art, and Design , University of the Philippines Cebu, 2024)
Film has the power to highlight issues faced by marginalized groups (Santiago, 1993). In the Philippines, renowned director Lino Brocka's social realist films, particularly during the Martial Law era, emphasized workers' struggles and resistance. Stuart Hall's (1973) Audience Reception Theory suggests that audiences interpret a film?s message differently based on their backgrounds. This qualitative research study analyzed the reception of unionized and non-unionized Cebuano production workers on labor unionism through Brocka's Bayan Ko: Kapit sa Patalim (1984) film. Two sets of ginabayang talakayan were conducted to analyze their (a) depiction of labor unionism in the film, (b) lived experiences with the film?s conflicts, (c) reception of the film?s message according to their decoding positions, and (d) backgrounds affecting these receptions. Based on their attitudes, beliefs, and values, our findings revealed that unionized workers received the film's message as intended, embracing themes of collectivism, resistance, and awareness. Contrarily, non-unionized workers interpreted it differently, manifesting individualism, conflict-avoidance, and indifference. However, some workers shared the same concepts of labor unionism grounded on their negotiated decoding positions: situation-dependent participation, priority-driven approaches, and consciousness-reliant perspective on union relevance. The study concluded that workers' receptions of the film were shaped by social, political, and economic factors.
Thesis (Bachelor of Arts in Communication)--UP Cebu, 21 May 2024.
Includes bibliographical references and appendices.